Systematic Review of Chemistry Educational Strategies and Curriculum Integration in Ocean Acidification - Ardi Widhia Sabekti; Nur Eka Kusuma Hindrasti (Jurnal Zarah, 2026)
This systematic literature review examines the trends and developments in ocean acidification education research from 2011 to 2025. Using the PRISMA methodology, 30 articles from the Scopus database were analyzed to identify key themes, research gaps, and future directions in teaching and learning about ocean acidification. The findings reveal a growing interest in integrating ocean acidification into science education curricula, with a significant emphasis on inquiry-based learning, technology-enhanced instruction, and interdisciplinary approaches. The United States leads research production (51 authors), followed by Spain, Sweden, and Greece. Key educational innovations include virtual reality applications, computational modelling, hands-on laboratory experiments, and collaborative learning strategies. With an average of 23.37 citations per document, this field has a substantial academic impact. However, challenges persist in terms of public awareness, teacher preparation, and curriculum integration. The review identifies the critical need for enhanced pedagogical resources, professional development programs, and assessment tools to effectively teach ocean acidification as a climate change issue. These findings provide valuable insights for educators, curriculum developers, and policymakers seeking to strengthen ocean and climate change education in formal and informal settings.